Energy Waste as a Side-Effect of Photovoltaic Development: Net Impact of Photovoltaics on CO2 Emissions in European Union Countries - Bożena Gajdzik; Radosław Wolniak; Rafał Nagaj; Brigita Žuromskaitė-Nagaj; Wiesław Grebski (Energies)
Decarbonization policies are being implemented in all EU countries where renewable energy is being developed. One of the main energy sources used for this purpose is photovoltaic energy. However, the development of photovoltaics does not only mean environmental benefits in the form of green energy and thus a reduction in greenhouse gas emissions from fossil fuel energy production, but also energy waste. The development of photovoltaics generates energy waste, some of which cannot be recovered, which in turn has a negative impact on gas emissions. The aim of this article is to analyse the amount of energy waste from photovoltaics in European Union countries and the net impact of photovoltaics on greenhouse gas emissions. Data sources are Eurostat and Our World In Data. The analysis will be carried out for the majority of EU countries, excluding the smallest countries whose data may distort the overall results. The analysis should show the overall impact of PV in the countries analysed and the changes over the period studied. The results will also indicate whether the impact of PV on decarbonization is similar across the EU countries analysed, or whether there are clusters of countries due to the impact of PV, or a negative impact in some of them.